The end of the Chinese "Middle Ages" essays in Mid-Tang literary culture - Owen, Stephen 1946- (Stanford Univ. Press, 1996)
This book explores, through a series of essays, a set of interrelated elements that define the literary culture of China in the late eighth and early ninth centuries. This period, known as the Mid-Tang, broke with many of the intellectual habits of the 'middle period' of Chinese culture and adumbrated many of the characteristics of China in the Song and later periods. Issues examined include the problem of 'singularity', or representations of identity as an assertion of superiority over others, different ways of representing landscapes and domestic activities, and changing perceptions in the status and role of the writer and poet as an artist.
Keywords: Geschichte 618-907; Chinees; Letterkunde; Littérature chinoise - 618-907 (Dynastie des Tʻang); Poésie chinoise - 618-907 (Dynastie des Tʻang); Literatur; Chinese literature -- Tʻang dynasty, 618-907 -- History and criticism; Chinese poetry -- Tʻang dynasty, 618-907 -- History and criticism; Civilization, Medieval, in literature; Tangdynastie; Chinesisch; Chine - Vie intellectuelle - 221 av. J.C.-960; China -- Intellectual life -- 221 B.C.-960 A.D